Assessing water tenure security and livelihoods of highland people in northern Thailand - Chapika Sangkapitux (2018)
In this article, water tenure security in a highland watershed of northern Thailand is assessed by means of a Water Security Index (WSI) developed along three dimensions, namely (1) diversity of available water sources, (2) access to those sources expressed as a percentage of land irrigated and (3) risks of conflicts and water scarcity. Results suggest that water security of upstream communities was significantly lower than that of the downstream communities, with negative implications for the sustainability of their livelihoods. Our results provide evidence against the general perception among lowland people and policy-makers that upstream communities enjoy an abundance of water resources and are primarily responsible for water scarcity and other negative externalities felt by downstream populations. Our study suggests that this perception needs to be revised and that environmental policy planning should incorporate water security aspects.